Age of Acquisition and Spoken Words: Examining Hemispheric Differences in Lexical Processing. (March 2023) - González-Alvarez, Julio; Cervera-Crespo, Teresa
The relationship between the age of acquisition (AoA) of words and their cerebral hemispheric representation is controversial because the experimental results have been contradictory. However, most of the lexical processing experiments were performed with stimuli consisting of written words. If we want to compare the processing of words learned very early in infancy—when children cannot read—with words learned later, it seems more logical to employ spoken words as experimental stimuli. This study, based on the auditory lexical decision task, used spoken words that were classified according to an objective criterion of AoA with extremely distant means (2.88 vs. 9.28 years old). As revealed by the reaction times, both early and late words were processed more efficiently in the left hemisphere, with no AoA × Hemisphere interaction. The results are discussed from a theoretical point of view, considering that all the experiments were conducted using adult participants.